اثر استخدام تكنولوجيا المعلومات على جودة المراجعة الخارجية - سارة, مهري; سهيلة, حجايجي; رحمة, بوسنينة; مصطفى, حنكه (University of eloued جامعة الوادي, 2022)
"الملخص تهدف هذه الدراسة للتعرف على أثر استخدام تكنولوجيا المعلومات على جودة المراجعة الخارجية، وذلك من خلال دراسة ميدانية لعينة من مراجعي الحسابات، وكذا الأستاذة الجامعين المتخصصين في ميدان المراجعة ولتحقيق هذا الهدف تم تقسيم الدراسة إلى جزئين، جزء نظري تكون من فصلين من أجل التأصيل النظري الموضوع، والجزء التطبيقي خصص لاختبار فروض الدراسة من خلال التحليل الإحصائي البيانات التي تم جمعها من خلال الاستبانات الموزعة . وقد توصلت الدراسة على إن يستوجب لمراجع الحسابات التمتع بالكفاءة العلمية والتدريب العملي للازم في محال تكنولوجيا المعلومات، احتكاك مراجع الحسابات بمكاتب المراجعة يساعد في تحسين كفاءته العلمية والعملية، أيضا يمثل استقلال مراجع الحسابات حجر الزاوية في ممارسته لمهنته في ظل بيئة تكنولوجيا المعلومات، وان استخدام تكنولوجيا المعلومات تؤثر على جودة المراجعة الخارجية. وقد أوصت الدارسة على تعزيز أهمية استعمال تكنولوجيا المعلومات في عملية المراجعة الخارجية، ضرورة قيام اقيات المنظمة لمهنة المراجعة في الجزائر بتحديث القوانين والأنظمة، خاصة فيما يتعلق بالمراجعة الخارجية في بيئة تكنولوجيا المعلومات، ضرورة إلمام مراجع الحسابات الخارجي بمخاطر المراجعة بحدف تفاديها ومعالجتها، ضرورة إنشاء هيئة مستقلة تابعة للغرفة الوطنية لمراجعي الحسابات تعمل على مراقبة جودة المراجعة الخارجية في بيئة تكنولوجيا المعلومات. ""Abstract: This study aims to identify the impact of the use of information technology on the quality of external auditing through a field study of a sample of auditors as well as a university. professor specialized in the field of auditing. And the practical part was devoted to testing the hypotheses of the study through statistical analysis of the data collected through distributed questionnaires. The study concluded that it is necessary for the auditor to enjoy the scientific competence and practical training necessary in the field of information technology. The auditor's contact with audit offices helps in improving his scientific and practical efficiency. The auditor's: independence also represents the cornerstone in his practice of his profession in the light of the information technology environment and that the use of technology Information affects the quality of the external audit. The study recommended to enhance the importance of using information technology in the external audit process the need for the bodies regulating the audit profession in Algeria to update laws and regulations especially with regard to external audit in the information technology environment the need for the external auditor to be aware of audit risks in order to avoid and address them the need to establish an authority An independent subsidiary of the National Chamber of Auditors works to monitor the quality of external audit in the IT environment. "
ماستر محاسبة وتدقيق
Keywords: تكنولوجيا المعلومات، مراجعة الحسانات الخارجية، مراجع الحسابات الخارجي، جودة المراجعة; Information technology,، external audit ،external auditor، audit quality